Methodology for the development of 3D geotechnical models using ordinary kriging - Ramírez Castañeda, Jose Luis (2023)
Currently, there are few studies that apply geostatistical simulation methods to model the geomechanical properties of rock masses, and most of these studies overlook the anisotropy of the geotechnical data. Therefore, the objective of the present study is to develop a 3D geotechnical model using geostatistical techniques and thereby establish the geotechnical parameters used to identify geotechnical zones with potential risk. This article presents a characterization methodology based on geostatistical simulation of geotechnical variables. In this sense, initially the geotechnical log data of the 532 drill holes drilled in the open pit located in the mining district of Tintaya (Espinar, Cusco) were reviewed, performing the exploratory analysis and spatial distribution analysis of geotechnical variables (spacing, FF/m, RMR, RQD and UCS), from this information the input variables were selected for the development of the block model. From the estimates made to generate the three-dimensional geomechanical block model (RMR, RQD and UCS), an evaluation of the quality and characterization of the rock mass of the study area was achieved and a methodology was developed to reduce the uncertainties related to the high spatial variability of the geotechnical sectorization, due to the geostatistical techniques used.